2020
DOI: 10.1111/jvp.12853
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacokinetics and bioavailability of marbofloxacin in geese (Anser Anser domesticus) after two sites of intramuscular administrations

Abstract: The pharmacokinetics of marbofloxacin (MAR) was compared in geese (Anser Anser domesticus) after single intravenous (IV) and intramuscular (IM) (thigh and pectoral muscles) administrations of 5 mg/kg. Serum concentrations of MAR were determined with high‐performance liquid chromatography (HPLC) method. Serum MAR concentrations versus time were analyzed by a noncompartmental method. After IV administration, MAR showed high volume of distribution at steady state (Vdss) of 5.24 ± 1.08 L/kg. The serum body clearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…To the best of our knowledge, this study is the first to investigate the effect of IM injection sites on the pharmacological profile of AMOX in fish, specifically in olive flounder. However, the effects of various IM injection sites on PK have been previously reported in terrestrial animals, such as piglets, sheep, horses, and geese [15][16][17][18]. Sooud et al [18] demonstrated that IM injection of marbofloxacin into the thigh muscle of geese produced a higher maximum drug concentration than injection into the pectoral muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this study is the first to investigate the effect of IM injection sites on the pharmacological profile of AMOX in fish, specifically in olive flounder. However, the effects of various IM injection sites on PK have been previously reported in terrestrial animals, such as piglets, sheep, horses, and geese [15][16][17][18]. Sooud et al [18] demonstrated that IM injection of marbofloxacin into the thigh muscle of geese produced a higher maximum drug concentration than injection into the pectoral muscle.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of various IM injection sites on PK have been previously reported in terrestrial animals, such as piglets, sheep, horses, and geese [15][16][17][18]. Sooud et al [18] demonstrated that IM injection of marbofloxacin into the thigh muscle of geese produced a higher maximum drug concentration than injection into the pectoral muscle. Furthermore, when penicillin G was injected into horses, the neck area was found to be advantageous for drug absorption [17], and a similar trend was observed when AMOX was injected into sheep [16].…”
Section: Discussionmentioning
confidence: 99%